1992
DOI: 10.1111/j.1365-2885.1992.tb00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of amoxicillin administered intravenously to sheep and goats

Abstract: The pharmacokinetic behavior of sodium amoxicillin was studied after intravenous administration to six sheep and five goats to determine if there are species differences in disposition. The plasma drug concentrations vs. time following intravenous administration of 10 mg/kg were best described by the biexponential equations Cp = 42.9e-0.077.t + 3.68e-0.0134.t for goats, and Cp = 53.5e-0.06.t + 1.69e-0.015.t for sheep. The terminal disposition half-lives for sheep and goats were 46.3 and 66.9 min respectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
1
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 7 publications
(2 reference statements)
8
23
1
1
Order By: Relevance
“…The difference in rate of excretion of clavulanic acid reflected in the clearance values may be due to differences in the elimination half-life (ij^) of the drug, but this was not the case with amoxicillin. The body clearances of amoxicillin in both species were found to be slower than that reported by Dorrestein et al (1987) in pigeons, and somewhat faster than that found in some mammals (Craigmill et al, 1992;Montesissa et al, 1988).…”
Section: Discussionmentioning
confidence: 61%
“…The difference in rate of excretion of clavulanic acid reflected in the clearance values may be due to differences in the elimination half-life (ij^) of the drug, but this was not the case with amoxicillin. The body clearances of amoxicillin in both species were found to be slower than that reported by Dorrestein et al (1987) in pigeons, and somewhat faster than that found in some mammals (Craigmill et al, 1992;Montesissa et al, 1988).…”
Section: Discussionmentioning
confidence: 61%
“…They (n = 9) received 5 g of the drug, containing 75 mg of AMP sodium in physiological solution, through a syringe tube by intramammary administration. Following single intramammary administration, the milk samples (5 mL) were collected after 2, 4,6,8,10,24, 36, 48, and 60 h. The liquid chromatography-mass spectrometry analysis was performed on the Agilent 1200 system connected to an AB Sciex API 4000™ mass spectrometer. The pharmacokinetic analysis of the concentrations of the antibiotic in milk was performed using software Phoenix ® WinNonlin ® 6.4.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of amoxicillin in the chicken followed a two-compartment open model in view of the bi-exponential decline of plasma amoxicillin concentrations; this kinetic disposition was similar to that described previously in man, cows, mares, horses, dogs, and sheep and goats. [13][14][15][16][17][18] Following intravenous administration, the disappearance of the drug from the plasma of chickens was characterized by an initial rapid distribution phase (t0.5α) 0.22 h for both groups; followed by a slower elimination phase (t0.5β) 8.05 and 6.71 h for both groups, respectively. The results indicate that amoxicillin distributed more quickly after intravenous dosing.…”
Section: Discussionmentioning
confidence: 99%
“…After the IV dose of 20 mg/kg, the (t0.5β) observed for amoxicillin in chickens was substantially greater than that reported for pigeons, dogs, sheep and goats, cows, buffalo calves, horses and humans where the range of reported values for (t0.5β) is 45 min for pigeon and sheep to 2 h for buffalo calves. [18][19][20] This could be due to differences in protein binding, biotransformation and excretion of the antibiotic. Earlier studies on the excretion of amoxicillin have demonstrated that this drug is eliminated mainly via urine and bile in other species of domestic animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation